Interleukin-13 Inhibitors in the Treatment of Atopic Dermatitis: The Role of Tralokinumab - Annunziata Dattola; Martina Tolone; Emanuele Amore; Luigi Bennardo; Simone Amato; Teresa Grieco; Antonio Giovanni Richetta; Giovanni Pellacani; Nevena Skroza; Steven Paul Nisticò (Mattioli1885, 2024)
Introduction: The advent of biotechnological drugs has significantly changed the management of atopic dermatitis (AD) and the approach to the moderate-to-severe form of this chronic relapsing disease. Objectives: The aim of our review is to summarize the current literature on anti-interleukin (IL)-13 in atopic dermatitis. Methods: A literature search was organized and a systematic review was performed to summarize the most recent evidence supporting the efficacy and safety of tralokinumab. Results: Tralokinumab (anti-IL-13) 300 mg every 2 weeks subcutaneously has proven effective in several clinical trials in adults and adolescents with moderate to severe atopic dermatitis inadequately controlled with other topical or systemic therapies. Tralokinumab was found to be significantly superior in terms of efficacy in reducing IGA, EASI-75, NRS pruritus, and DLQI scale numbers. During follow-up, tralokinumab was well tolerated with limited severity of adverse events. Conclusion: Tralokinumab leads to statistically significant improvements in disease severity and outcome scores. It represents an effective treatment option for adults with moderate to severe AD, but further large-scale studies are needed to verify long-term superiority over other treatments.